Buying and Selling Cosmetics Not Labeled Halal in Bitung City Perspective of Muamalah Jurisprudence - Yusuf, Nasruddin; Botutihe, Magfirah; Gonibala, Pedro Muhammad Arfi (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
Bitung City is a city located in North Sulawesi whose residents have a high interest in maintaining the performance of their appearance, both women and men. To get a good and beautiful performance and appearance, it is necessary to use beauty tools and cosmetics that support their appearance. The problem is that some cosmetics that are marketed do not have a halal label so they become safe and halal for use in the lens of Islamic law. Some respondents in Bitung City have different views regarding the law on the sale and purchase of cosmetics that are not labeled halal. From the results of the study, it was found that some Muslim users and sellers do not care about the halal label or not in cosmetic products, the most important thing for them is that it has been standardized safe for health issued by BPPOM RI, so in their view it is okay to buy and sell this kind of Some others view the provisions of halal law in products marketed as what causes buying and selling to be legal and halal according to Islamic law. Because the cosmetics marketed are not labeled halal, the cosmetics have the status of sunhat or doubt halalala. Therefore, buying and selling are also categorized as a syubhat buying and selling. Shubhat buying and selling is included in the category of buying and selling that is gharar or vague because of the uncertainty of the legal status of the contents contained in the cosmetics, whether halal or haram. Buying and selling gharar is buying and selling prohibited in the provisions of Islamic Sharia. Keywords: Cosmetics, Buying and Selling, and Review of Muamalah Jurisprudence